MENUJU MASYARAKAT BERDAYA: MEMBEDAH PENDEKATAN SELF-HELP DAN TECHNOCRATIC PADA DESA SIDOSERMO DAN DESA BATU MALANG - Al Haniva, Sophia; Putri Dewanti, Arinta (Fisip UIN Sunan Gunung Djati Bandung, 2024)
The community empowerment approach is a major factor in policy-making to implement development that involves the community. As carried out by Diskumdag Batu City in the village in Batu City Malang which empowers its community through SMEs. In addition, Sidosermo Indah Surabaya Village also carried out a strategy to increase the potential of its village through a special needs community called